Proceedings of the 2017 EMNLP Workshop: Natural Language Processing Meets Journalism 2017
DOI: 10.18653/v1/w17-4205
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Attitudes to Climate Change in the Media using sentiment analysis based on Latent Dirichlet Allocation

Abstract: News media typically present biased accounts of news stories, and different publications present different angles on the same event. In this research, we investigate how different publications differ in their approach to stories about climate change, by examining the sentiment and topics presented. To understand these attitudes, we find sentiment targets by combining Latent Dirichlet Allocation (LDA) with SentiWordNet, a general sentiment lexicon. Using LDA, we generate topics containing keywords which represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…Results are plotted in particular for correlations of emotions and topics and the role of "influencers" versus less prominent accounts. Jiang et al (2017) gathered 11,000 newspaper articles from four British broadsheets over the years 2007-2016. The search criterion was that cc has to occur at least three times.…”
Section: Discourse: Research In the Nlp Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…Results are plotted in particular for correlations of emotions and topics and the role of "influencers" versus less prominent accounts. Jiang et al (2017) gathered 11,000 newspaper articles from four British broadsheets over the years 2007-2016. The search criterion was that cc has to occur at least three times.…”
Section: Discourse: Research In the Nlp Communitymentioning
confidence: 99%
“…Summary In the absence of any "standard CC dataset", the NLP research so far has been scattered. Types of target texts (Discourse 1 ) were limited to news (Jiang et al, 2017;Luo et al, 2020), blogs Salway et al, 2016) and Twitter (Pathak et al, 2017;Koenecke and Feliu-Fabà, 2020); no comparisons across genres or channels were made, and there was no attention on political arenas or on statements by individuals and interest groups that are meant to directly influence policy-making. In terms of methods and goals we found network analysis for detecting communities (Salway et al, 2016;Pathak et al, 2017), sentiment/stance classification for Discourse 2 grouping Pathak et al, 2017;Jiang et al, 2017;Luo et al, 2020;Koenecke and Feliu-Fabà, 2020), topic modeling for computing topic/sentiment correlations (Jiang et al, 2017), and fine-grained framing distinction (Luo et al, 2020).…”
Section: Discourse: Research In the Nlp Communitymentioning
confidence: 99%
“…However, there has been limited application of sentiment analysis techniques for analyzing opinions about climate change policies in mass and social media. For example, (Jiang et al, 2017) assess the public perception and sentiments regarding climate change and adaptive and mitigating measures like renewable energy. Dahal et al (2019) and Loureiro and Alló (2020) have employed sentiment analysis techniques for analyzing tweets on climate change.…”
Section: Media Content Analysis For Climate Change Via Topic Modelingmentioning
confidence: 99%
“…Print media and social media texts have also been analyzed extensively in the NLP community via a number of tasks like opinion mining (Ravi and Ravi, 2015), controversy detection Dori-Hacohen, 2015), fake news detection (Zhou and Zafarani, 2020;Thorne et al, 2017), argument mining (Lippi and Torroni, 2016), stance detection (Ghosh et al, 2019;Küc ¸ük and Can, 2020), perspective identification (Wong et al, 2016), inter alia. Researchers have recently started exploring media's perception on climate issues (Jiang et al, 2017;Luo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that data from Twitter are relevant to climate events and valuable for measuring opinion polarization [9], [12], [13]. Due to the absence of large annotated datasets in different climate change-related topics, most previous works took an unsupervised learning fashion [14], [15] to classify tweets into topic categories. These methods use topic models to obtain extractive topic words, then map the topic words to major topic categories by the semantics of the topic words.…”
Section: Introductionmentioning
confidence: 99%